Continuous flow synthesis of azobenzenes via Baeyer–Mills reaction - Griwatz, Jan H.; Kunz, Anne; Wegner, Hermann A. (Beilstein Journal of Organic Chemistry, 2022)
Azobenzene, as one of the most prominent molecular switches, is featured in many applications ranging from photopharmacology to information or energy storage. In order to easily and reproducibly synthesize non-symmetric substituted azobenzenes in an efficient way, especially on a large scale, the commonly used Baeyer–Mills coupling reaction was adopted to a continuous flow setup. The versatility was demonstrated with a scope of 20 substances and the scalability of this method exemplified by the synthesis of >70 g of an azobenzene derivative applied in molecular solar thermal storage (MOST) systems.
Keywords: azobenzenes; Baeyer–Mills reaction; continuous flow; molecular switches; solar fuel

(untitled) - Wang, Z.; Losantos, R.; Sampedro, D.; Morikawa, M.-a.; Börjesson, K.; Kimizuka, N.; Moth-Poulsen, K. (J. Mater. Chem. A, 2019)

(untitled) - Liu, Z. F.; Hashimoto, K.; Fujishima, A. (Nature, 1990)

(untitled) - Ikeda, T.; Tsutsumi, O. (Science, 1995)

(untitled) - Gerkman, M. A.; Han, G. G. D. (Joule, 2020)

(untitled) - Dong, L.; Feng, Y.; Wang, L.; Feng, W. (Chem. Soc. Rev., 2018)

(untitled) - Liu, H.-d.; Zheng, A.-x.; Gong, C.-b.; Ma, X.-b.; Hon-Wah Lam, M.; Chow, C.-f.; Tang, Q. (RSC Adv., 2015)

(untitled) - Hüll, K.; Morstein, J.; Trauner, D. (Chem. Rev., 2018)

(untitled) - Liu, M.; Yan, X.; Hu, M.; Chen, X.; Zhang, M.; Zheng, B.; Hu, X.; Shao, S.; Huang, F. (Org. Lett., 2010)

(untitled) - Konieczkowska, J.; Bujak, K.; Nocoń, K.; Schab-Balcerzak, E. (Dyes Pigm., 2019)

(untitled) - Zhang, Y.; Sun, X.; An, X.; Sui, A.; Yi, J.; Song, X.-m. (Dyes Pigm., 2021)

(untitled) - Norikane, Y.; Tamaoki, N. (Org. Lett., 2004)

(untitled) - Hartley, G. S. (Nature, 1937)

(untitled) - Harada, J.; Ogawa, K.; Tomoda, S. (Acta Crystallogr., Sect. B: Struct. Sci., 1997)

(untitled) - Mostad, A.; Rømming, C. (Acta Chem. Scand., 1971)

(untitled) - Bandara, H. M. D.; Burdette, S. C. (Chem. Soc. Rev., 2012)

(untitled) - Merino, E. (Chem. Soc. Rev., 2011)

(untitled) - Zhang, C.; Jiao, N. (Angew. Chem., Int. Ed., 2010)

(untitled) - Mills, C. (J. Chem. Soc., Trans., 1895)

(untitled) - Baeyer, A. (Ber. Dtsch. Chem. Ges., 1874)

(untitled) - Ueno, K.; Akiyoshi, S. (J. Am. Chem. Soc., 1954)

(untitled) - Dommaschk, M.; Peters, M.; Gutzeit, F.; Schütt, C.; Näther, C.; Sönnichsen, F. D.; Tiwari, S.; Riedel, C.; Boretius, S.; Herges, R. (J. Am. Chem. Soc., 2015)

(untitled) - Plutschack, M. B.; Pieber, B.; Gilmore, K.; Seeberger, P. H. (Chem. Rev., 2017)

(untitled) - Qin, H.; Liu, C.; Lv, N.; He, W.; Meng, J.; Fang, Z.; Guo, K. (Dyes Pigm., 2020)

(untitled) - Georgiádes, Á.; Ötvös, S. B.; Fülöp, F. (ACS Sustainable Chem. Eng., 2015)

(untitled) - Tombari, R. J.; Tuck, J. R.; Yardeny, N.; Gingrich, P. W.; Tantillo, D. J.; Olson, D. E. (Org. Biomol. Chem., 2021)

(untitled) - Masutani, K.; Morikawa, M.-a.; Kimizuka, N. (Chem. Commun., 2014)

(untitled) - Wang, Z.; Moïse, H.; Cacciarini, M.; Nielsen, M. B.; Morikawa, M.-a.; Kimizuka, N.; Moth‐Poulsen, K. (Adv. Sci., 2021)